Immunological study of COVID-19 vaccine candidate based on recombinant spike trimer protein from different SARS-CoV-2 variants of concern - Rudi, Erika; Martin Aispuro, Pablo; Zurita, Eugenia; Gonzalez Lopez Ledesma, Maria M.; Bottero, Daniela; Malito, Juan; Gabrielli, Magali; Gaillard, Emilia; Stuible, Matthew; Durocher, Yves; Gamarnik, Andrea V.; Wigdorovitz, Andrés; et al. (Frontiers in Immunology, 2022)
The emergency of new SARS-CoV-2 variants that feature increased immune escape marks an urgent demand for better vaccines that will provide broader immunogenicity. Here, we evaluated the immunogenic capacity of vaccine candidates based on the recombinant trimeric spike protein (S) of different SARS-CoV-2 variants of concern (VOC), including the ancestral Wuhan, Beta and Delta viruses. In particular, we assessed formulations containing either single or combined S protein variants. Our study shows that the formulation containing the single S protein from the ancestral Wuhan virus at a concentration of 2 µg (SW2-Vac 2 µg) displayed in the mouse model the highest IgG antibody levels against all the three (Wuhan, Beta, and Delta) SARS-CoV-2 S protein variants tested. In addition, this formulation induced significantly higher neutralizing antibody titers against the three viral variants when compared with authorized Gam-COVID-Vac-rAd26/rAd5 (Sputnik V) or ChAdOx1 (AstraZeneca) vaccines. SW2-Vac 2 µg was also able to induce IFN-gamma and IL17, memory CD4 populations and follicular T cells. Used as a booster dose for schedules performed with different authorized vaccines, SW2-Vac 2 µg vaccine candidate also induced higher levels of total IgG and IgG isotypes against S protein from different SARS-CoV-2 variants in comparison with those observed with homologous 3-dose schedule of Sputnik V or AstraZeneca. Moreover, SW2-Vac 2 µg booster induced broadly strong neutralizing antibody levels against the three tested SARS-CoV-2 variants. SW2-Vac 2 µg booster also induced CD4+ central memory, CD4+ effector and CD8+ populations. Overall, the results demonstrate that SW2-Vac 2 µg is a promising formulation for the development of a next generation COVID-19 vaccine.